TAX TRANSPARENCY FRAMEWORK: REKONSTRUKSI KONSEPTUAL INDIKATOR AKUNTANSI KEUANGAN UNTUK GOOD CORPORATE GOVERMANCE - Hidayatullah, Muhammad Baharudin Yusuf Hidayatullah; Shofiatul Jannah, Binti (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
Tax transparency is a crucial aspect of modern corporate governance, serving as an indicator of corporate accountability and reputation. This study develops a Tax Transparency Framework, a conceptual framework that integrates financial accounting indicators with Good Corporate Governance (GCG) principles to improve the quality of tax disclosure. The approach used is a literature-based conceptual one, with analysis of accounting standards, tax regulations, and previous research. The results of the study show that effective tax disclosure needs to include quantitative dimensions such as current and deferred tax expenses, fiscal reconciliation, and effective tax rates, as well as qualitative dimensions, including tax policy and regulatory compliance. The integration of accounting indicators and Good Corporate Governance principles produces a framework that functions as an internal control mechanism (agency theory) as well as a means of obtaining social legitimacy (legitimacy theory). This framework provides officers with practical guidance for companies in preparing comprehensive tax reports and serves as a regulatory reference for the development of tax disclosure standards, thereby increasing stakeholder trust and company reputation.